2017
DOI: 10.1007/s00402-017-2764-1
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes of intramedullary nailing for diaphyseal atypical femur fractures: is it safe to modify a nail entry in bowed femur?

Abstract: Changing the entry point laterally allowed the nail to be accommodated in bowed femurs, decreasing the risk of deformity and improving healing time. In severely varus femur, the lateral entry of the straight nail can be a useful technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“… 17) Several modified operation techniques including far lateral entry point, use of the opposite site nail, overreaming more than 2.5 mm have been introduced to overcome excessive anterolateral bowing of the femur. 9 10 22) Even if an IM nail is inserted after addressing these difficulties, leg-length discrepancy caused by femoral straightening and lengthening is inevitable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 17) Several modified operation techniques including far lateral entry point, use of the opposite site nail, overreaming more than 2.5 mm have been introduced to overcome excessive anterolateral bowing of the femur. 9 10 22) Even if an IM nail is inserted after addressing these difficulties, leg-length discrepancy caused by femoral straightening and lengthening is inevitable.…”
Section: Discussionmentioning
confidence: 99%
“…Also, several surgical methods have been proposed to overcome excessive femoral bowing. 9 10) Despite these efforts to use IM nails, iatrogenic fracture during the insertion of IM nails and leg length discrepancy due to straightening of the bowed femur are expected complications.…”
mentioning
confidence: 99%
“…7 ). Kim et al 17) reported that, upon comparing the results of using a lateral entry point beginning at the greater trochanter and the original entry point for intramedullary nail insertion in patients with atypical femoral shaft fracture accompanied by severe anterolateral bowing, there was no observed difference in the degree of union, however, the time to union was significantly reduced.…”
Section: Methods To Overcome Anterolateral Femoral Bowingmentioning
confidence: 99%
“…In most cases a medullary nail is placed to provide fixation of the fracture and allow healing. For patients with bowed femurs, an alternative nail entry site may be necessary [22], and lateral fixation has been suggested as an alternative [23]. In any event, surgery followed by a rehabilitation program is necessary for those who have had a complete fracture; it is possible that the surgical technique will be refined over time.…”
Section: Management Of Atypical Femoral Fracturesmentioning
confidence: 99%